2014
DOI: 10.1111/jan.12444
|View full text |Cite
|
Sign up to set email alerts
|

Developing a pressure ulcer risk factor minimum data set and risk assessment framework

Abstract: AimTo agree a draft pressure ulcer risk factor Minimum Data Set to underpin the development of a new evidenced-based Risk Assessment Framework.BackgroundA recent systematic review identified the need for a pressure ulcer risk factor Minimum Data Set and development and validation of an evidenced-based pressure ulcer Risk Assessment Framework. This was undertaken through the Pressure UlceR Programme Of reSEarch (RP-PG-0407-10056), funded by the National Institute for Health Research and incorporates five phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 30 publications
7
76
0
Order By: Relevance
“…In keeping with those who used structured consensus methods in the development of pressure ulcer risk assessment MDS [35], the method provided a transparent approach to the development of a generic wound assessment MDS, informed, in this case by a literature review (rather than a more robust systematic review) and the opinions of experts in the field. The discussions of the expert group face-to-face meeting allowed challenges and differences in opinion to be explored and understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with those who used structured consensus methods in the development of pressure ulcer risk assessment MDS [35], the method provided a transparent approach to the development of a generic wound assessment MDS, informed, in this case by a literature review (rather than a more robust systematic review) and the opinions of experts in the field. The discussions of the expert group face-to-face meeting allowed challenges and differences in opinion to be explored and understood.…”
Section: Discussionmentioning
confidence: 99%
“…A modified RAND/UCLA (Research and Development/University of California at Los Angeles) appropriateness method [34] based on a previous consensus study was used [35]. This incorporated faceto-face interaction of an expert group and pre-and post-meeting questionnaire completion (incorporating 9 point Likert scales) considering what should be included in a generic wound assessment MDS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of these conclusions underlines most definitions of pressure ulcers which describe the action of pressure, friction or shearing forces, or the synonym "pressure sore" is used for pressure ulcer. Coleman et al (2014) found a close relationship between immobility, friction and shear, but they also drew attention to difficulties in measuring these risk factors in clinical practice. Imbalanced nutritional state was rated as the third most significant risk factor for pressure ulcer development by the nurses.…”
Section: Discussionmentioning
confidence: 99%
“…-2017. There might be a problem in identification of the risk factor mechanical factors (e.g., shearing forces, pressure, restraint), which was also illustrated by Coleman et al (2014) related to difficulties with its measurement in clinical practice. In research studies, pressure ulcer risk prediction focuses on the use of the standardized tools which, however, have various levels of validity and reliability.…”
Section: Discussionmentioning
confidence: 99%